AUTOMATED ELECTRICAL SYSTEMS OF ROBOTICS AREAS OF APPLICATION OF PROCEDURES (American Journal of Research in Humanities and Social Sciences, 2023)
This article provides information on the areas of application of automated electrical systems of robotics and the use of automated electrical equipment in the textile and manufacturing industries.